Annexin A2 Regulates β1 Integrin Internalization and Intestinal Epithelial Cell Migration - Rankin, Carl R. (American Society for Biochemistry and Molecular Biology, 2013)
The gastrointestinal epithelium functions as an important barrier that separates luminal contents from the underlying tissue compartment and is vital in maintaining mucosal homeostasis. Mucosal wounds in inflammatory disorders compromise the critical epithelial barrier. In response to injury, intestinal epithelial cells (IECs) rapidly migrate to reseal wounds. We have previously observed that a membrane-associated, actin binding protein, annexin A2 (AnxA2), is up-regulated in migrating IECs and plays an important role in promoting wound closure. To identify the mechanisms by which AnxA2 promotes IEC movement and wound closure, we used a loss of function approach. AnxA2-specific shRNA was utilized to generate IECs with stable down-regulation of AnxA2. Loss of AnxA2 inhibited IEC migration while promoting enhanced cell-matrix adhesion. These functional effects were associated with increased levels of β1 integrin protein, which is reported to play an important role in mediating the cell-matrix adhesive properties of epithelial cells. Because cell migration requires dynamic turnover of integrin-based adhesions, we tested whether AnxA2 modulates internalization of cell surface β1 integrin required for forward cell movement. Indeed, pulse-chase biotinylation experiments in IECs lacking AnxA2 demonstrated a significant increase in cell surface β1 integrin that was accompanied by decreased β1 integrin internalization and degradation. These findings support an important role of AnxA2 in controlling dynamics of β1 integrin at the cell surface that in turn is required for the active turnover of cell-matrix associations, cell migration, and wound closure.